Determinan terhadap Penyembuhan Luka Perineum pada Ibu Nifas di Praktik Mandiri Bidan Kota Palangkaraya: Determinants of Perineum Wound Healing on Post Partum Mother at Independent Practice of Midwives Palangka Raya City - Yuniarti, Yuniarti; Asi, Cahaya; Aprilia, Dea; Veronika, Sherly (Jurnal Surya Medika (JSM), 2021)
Maternal mortality in Indonesia related to childbirth is 11% infection starting from poor management of perineal rupture. Approximately 85% of women who deliver vaginally have perineal trauma, and less than 1% of episiotomy or perineal ruptures have an infection. The general objective of this study was to analyze the factors that influence the healing of perineal wounds in postpartum women. This research is an analytic observational with a cross-sectional design. The sampling technique used is purposive sampling. The sample of this study was postpartum women who experienced a second-degree perineal rupture in PMB in the Palangka Raya City. The results of the Chi-Square test analysis showed a significant relationship between education (p-value = 0.010), nutritional status (p-value = 0.001), and hemoglobin levels (0.000) with the duration of perineal wound healing. There is a relationship between education, nutritional status, and hemoglobin levels on perineal wound healing.